Preparation for Meaningful Work and Life: Urban High School Youth’s Reflections on Work-Based Learning 1 Year Post-Graduation - Kenny, Maureen E.; Catraio, Christine; Bempechat, Janine; Minor, Kelly; Olle, Chad; Blustein, David L.; Seltzer, Joanne (Frontiers in Psychology, 2016)
The challenges confronted by low-income high school students throughout school and across the transition to higher education and employment are well-documented in the United States and many other nations. Adopting a positive youth development (PYD) perspective (Lerner, Almerigi, Theokas, and Lerner, 2005), this study reports findings from interviews with 18 low-income, racially and ethnically diverse graduates of an urban Catholic high school in the U.S. The interviews were designed to shed light on the post-high school experiences of urban high school graduates and to understand how students construct meaning about the value of school and work-based learning (WBL) in their preparation for meaningful work and life. The interviews highlight the perceived value of the academic and noncognitive preparation students experienced through high school and WBL in relation to the challenges they encountered along the pathway to post-high school success and decent work. Overall, the findings suggest the potential of WBL for low-income youth in facilitating access to resources that build academic and psychological/noncognitive assets, while also illustrating the role of structural and contextual factors in shaping post-high school transitions and access to meaningful work and life opportunities.